Peningkatan Kemampuan Mengenal Konsep Bilangan Melalui Permainan Kartu Angka Di Taman Kanak-Kanak Plus Ridhotullah Padang - Sari, Nila; Wirman, Asdi (JFACE: Journal of Family, Adult, and Early Childhood Education, 2020)
This research is motivated by the low ability of children to recognize the concept of numbers, it is seen that in doing the tasks the child is still confused when grouping objects according to their numbers, and spelling out a number 1-10 is still irregular. The purpose of this study is to improve children's ability to recognize the concept of numbers through numbers card games. This type of research is classroom action research (CAR). Subjects for early childhood research group B totaled 15 children, consisting of 9 boys and 6 girls. This research was conducted in two cycles, each cycle having three meetings. Data collection techniques are observation and documentation and assessment results are processed using percentage techniques. The results showed during initial conditions, the value developed very well (BSB) the average percentage was 2.3%. In cycle I from meetings 1 to 3 the average percentage value increased to 9%, 15.3% and 22.3% but have not yet reached the KKM. In the second cycle of meetings 1 to 3 an increase was made because the numeric card game strategy was more attractive to children, this was evidenced by the average percentage values of 40%, 62% and 89% that had reached the KKM. It can be concluded that the number card game can improve the ability of children to recognize the concept of numbers in kindergarten Plus Ridhotullah Ulu Gadut Padang.